Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T16:14:14+01:00
X + 6y - 3x + 7y = 13y-2x

x - 6y - 2x - 7y - 5x =-6x - 13y

4y + 17x - 12y - 5z - 3x - 10z = -8y-15z+14x

-16a - 2b -4a - 9b - 7a = -27a-11b

-9a - 7b - 16x - 14y - 4b - 9x -2b = -9a-13b- 25x- 14y

-2x - 3 - x - 4 = -3x-7
1 5 1
2010-02-25T16:14:38+01:00
13y-2x
-13y-4x
8y+14x-15z
-27a-11b
-13b-9a-25x-14y
-3x-7
1 5 1
2010-02-25T16:17:54+01:00
X+6y-3x+7y=-2x+13y
x-6y-2x-7y-5x=-6x-13y
4y+17x-12y-5z-3x-10z=14x-8y-15z
-16a-2b-4a-9b-7a=-27a-11b
-9a-7b-16x-14y-4b-9x-2b=-9a-13b-25x-14y
-2x-3-x-4=-3x-7
1 5 1